Impacto de la Covid19 en las barreras percibidas para practicar actividad física en las personas usuarias de centros fitness en España - Santacruz Lozano, Jose Antonio; Jiménez Díaz-Benito, Víctor Jiménez Díaz-Benito; Cereijo Tejedor, Luis; Gonzalo Encabo, Paola; García, Borja; Jiménez-Beatty Navarro, José Emilio; Clemente Remón, Ángel Luis (Cuadernos de Psicología del Deporte, 2022)
This research intends to know the perceived barriers, as well as their predictor variables, in people who practice Physical Activity in fitness centers and were home confined due to the COVID-19 pandemic. The sample was conformed of 8,087 physical activity practitioners. An online questionnaire was administered by email. A descriptive analysis of the perceived barriers was done, and logistic regression analysis to determine possible predictor variables. The most important perceived barriers were price and a luck of security. Age, gender, the vigorous physical practice frequency and the observation of the WHO recommendations would be the predictor variables to a larger extend for the perceived barriers. The results are relevant for sport organizations to plan their services offer post lockdown.